2015
DOI: 10.1016/j.ajpath.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sphingosine Kinase Prevents Lipopolysaccharide-Induced Preterm Birth and Suppresses Proinflammatory Responses in a Murine Model

Abstract: Premature delivery occurs in 12% of all births, and accounts for nearly half of long-term neurological morbidity, and 60% to 80% of perinatal mortality. Despite advances in obstetrics and neonatology, the rate of premature delivery has increased approximately 12% since 1990. The single most common cause of spontaneous preterm birth is infection. Several lines of evidence have demonstrated the role of endothelin-1 as both a constrictor of uterine myometrial smooth muscle and a proinflammatory mediator. Endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…LPS induced preterm birth in mice is a well-established and relevant model for such investigation [20,21,22,23]. Timed pregnant Swiss Webster mice ( n = 11) were injected intraperitoneally on E15.5 ( t = 0) with LPS (serotype 026:B6, obtained from Sigma, 25 mg/kg) dissolved in PBS to induce preterm labor.…”
Section: Methodsmentioning
confidence: 99%
“…LPS induced preterm birth in mice is a well-established and relevant model for such investigation [20,21,22,23]. Timed pregnant Swiss Webster mice ( n = 11) were injected intraperitoneally on E15.5 ( t = 0) with LPS (serotype 026:B6, obtained from Sigma, 25 mg/kg) dissolved in PBS to induce preterm labor.…”
Section: Methodsmentioning
confidence: 99%
“…44 Several studies reporting the consequences of endothelin pathway blockade are presented in Table 2. [45][46][47] Other than those mentioned previously, naturally produced compounds or alternative therapeutics have recently been drawing attention as novel therapeutics for preterm birth since these substances possess strong anti-inflammatory properties. Some of them have been commonly administered as medicines for specific diseases with an inflammation-associated etiology in nonpregnant women.…”
Section: Substances Potentially Suppressing Inflammationmentioning
confidence: 99%
“…Various studies showed that SK1 is related to the progression of multiple tumors such as gastric cancer [Xiong et al, ], colorectal cancer [Shida et al, ], and hepatocellular carcinoma [Uranbileg et al, ]. SK1 is also relevant to inflammatory diseases [Price et al, ; Vyas et al, ; Jaigirdar et al, ]. The phosphorylation of SK1 and its subsequent translocation are critical steps for oncogenic signaling [Pitson et al, ].…”
Section: Introductionmentioning
confidence: 99%